1995
DOI: 10.3109/08990229509101503
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pain Perception after Anterior Capsulotomy: A Case Report

Abstract: The medial prefrontal cortex has been implicated in pain perception by recent anatomical, physiological, and functional imaging data demonstrating that frontal and anterior cingulate cortices receive inputs related to nociception; neurosurgical case reports suggest that lesions involving these areas may specifically reduce the affective or emotional component of chronic intractable pain. We examined this hypothesis more closely by assessing psychophysical ratings of (1) warmth, pain intensity, and unpleasantne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 51 publications
2
31
2
Order By: Relevance
“…Only when the figure was in or close to a horizontal orientation occipital gamma band power was increased. Thus, our experiment is in line with other studies in which Gestalt principles were Ž used to form an object, such as co-linearity Tallon et al, 1995;Tallon-Baudry et al, 1996 . Ž see also this volume , common motion Lutzen-.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Only when the figure was in or close to a horizontal orientation occipital gamma band power was increased. Thus, our experiment is in line with other studies in which Gestalt principles were Ž used to form an object, such as co-linearity Tallon et al, 1995;Tallon-Baudry et al, 1996 . Ž see also this volume , common motion Lutzen-.…”
Section: Discussionsupporting
confidence: 79%
“…We consider this to be an indicator of the activity of wide spread cell assemblies with members in subcortical Ž . limbic and neocortical structures related to the processing of emotional material as suggested by Ž several authors Damasio, 1998;Davidson, 1995Davidson, , 1998Davidson and Hugdahl, 1995;De Pascalis, 1989;Derryberry and Tucker, 1992;Lang et al, 1998;LeDoux, 1995a;Liotti and Tucker, 1995;Talbot et al, 1995;Tucker, 1984;Tucker and . Dawson, 1984 .…”
Section: Discussionmentioning
confidence: 99%
“…ACC neurons coding stimulus intensity have been found previously in the anesthetized rabbit (Sikes and Vogt, 1992). Furthermore, clinical data from patients with anterior cingulotomy (Davis et al, 1994) or deafferented anterior cingulate (Talbot et al, 1995) have also shown a diminished sensory coding ability. The only other region showing a similar SRF in our study was the primary sensory cortex.…”
Section: Stimulus Intensity-related Responsesmentioning
confidence: 84%
“…Its pivotal role within the nociceptive system has been established in lesion studies (Foltz and White, 1968;Bouckoms, 1989;Talbot et al, 1995) and in numerous functional neuroimaging studies using positron emission tomography (PET) (Jones et al, 1991;Talbot et al, 1991;Casey et al, 1994;Craig et al, 1996;Rainville et al, 1997;Coghill et al, 1999;Casey, 2000) and functional magnetic resonance imaging (fMRI) (Davis et al, 1997;Porro et al, 1998;Ploghaus et al, 1999;Kwan et al, 2000;Sawamoto et al, 2000). The ACC receives nociceptive inputs via medial thalamic nuclei and has been shown to code affective components of painful stimuli (Craig et al, 1996;Rainville et al, 1997;Sawamoto et al, 2000).…”
mentioning
confidence: 99%
“…Peyron et al (1998) suggested that the absence of ACC activation could be a speci®c feature for patients with allodynia after Wallenberg infarct, which may also be the case for allodynia after peripheral nerve damage. The lack of activation in the medial pain system, in contrast to the massive activations in the lateral pain system (7±9% rCBF increase in S1), was still an unexpected ®nding since the patient descriptions of dynamic mechanical allodynia usually include affective components (Hansson, 1994) and since the medial system is considered to be involved in processing the affective and evaluative part of the pain experience (Albe-Fessard et al, 1985;Vogt et al, 1993;Craig et al, 1994;Talbot et al, 1995;Willis, 1995;Rainville et al, 1997).…”
Section: Discussionmentioning
confidence: 99%